Service System and Marketing Strategy of PT Pegadaian Rappang Branch in Enhancing Customer Interest - Adam Latif; Rizky Noor Mohammad; Muhammad Aswar Arman; Indria Khairina; Fifi Lestari Sudirman (International Journal of Sustainable Applied Sciences, 2024)
This study examines the service system and marketing strategies of PT Pegadaian Rappang Branch to increase customer interest. The marketing strategy involves planning, pricing, promotion, and distribution. To remain competitive in the global market, modern marketing techniques such as cross-selling and up-selling are essential. PT Pegadaian Rappang Branch offers pawn-based credit and deposit services.The research targeted potential customers, including educational institutions and local communities, through socialization and promotional activities. These activities were carried out through direct interactions at Pegadaian offices and presentations at educational institutions. The findings indicate that a good service system includes clear procedures, professional staff, and adequate facilities. The socialization and promotion process received positive responses from the audience, who appreciated the assistance in understanding PT Pegadaian's products and financial management. The study concludes that fast and secure financial services, combined with effective marketing strategies and a robust service system, can significantly enhance consumer interest and understanding of PT Pegadaian's offerings. Moreover, these strategies help the company achieve its long-term goals of maintaining its market presence and improving societal welfare.